Ecobrick Menjadi Solusi Pemilahan Sampah Plastik - Ariandi, Indra Wahyu; Pangestu, Yuda Aji; Irsanra, Riaska; Agustin, Merlyn; Nareswari, Zhurifa; Ainunnisa, Desilia; Lutfi, Mohamad Bachtiar; Abdurrahman, Abdurrahman; Fatihah, Raisa; Saputra, Ronal Aji; Fauzan, Aris (Universitas Muhammadiyah Yogyakarta, 2025)
Dukuh Slametan, Gatak Village, Ngawen District, Klaten, faces significant challenges in managing plastic waste, most residents use the practice of burning waste as the main solution. In addition, the lack of awareness and lack of skills in implementing more environmentally friendly waste management practices is a significant challenge, so this community service program aims to provide a solution by introducing the Ecobrick method as a more sustainable alternative in managing plastic waste. This program uses a community-based participatory research (CBPR) approach, which includes socialization, focus group discussions (FGDs), Ecobrick making training, and monitoring and evaluation of community participation and program effectiveness. The main objective of this program is to increase community awareness and technical skills in making Ecobricks, with program results evaluated based on the level of participation and the number of Ecobricks successfully made. Of the 40 targeted residents, 30 people participated in the training, producing 44 ecobrick bottles which were then used to make three chairs for use in the surrounding environment. The evaluation results showed a substantial increase in community awareness of the detrimental consequences of burning plastic waste, accompanied by an appreciation of the benefits of ecobricks as an alternative solution, in addition, the program has succeeded in reducing the volume of plastic waste that was previously burned. However, several obstacles remain, including the scarcity of adequate plastic bottle raw materials, the challenge of achieving optimal ecobrick density, and the difficulty of fostering long-term commitment among residents to perpetuate the implementation of this methodology. To increase the effectiveness of the program, further support from the government and environmental organizations is needed, in the form of ongoing educational initiatives and incentives for active community participation. With a more systematic approach, ecobricks have the potential to become a sustainable solution that is implemented not only in Dusun Slametan, but also in other areas that face similar challenges in plastic waste management